Decreased FGF19 and FGF21: possible underlying common pathogenic mechanism of metabolic and cognitive dysregulation in depression - Mimi Tang; Mimi Tang; Shuqiao Cheng; Shuqiao Cheng; Lu Wang; Hui Tang; Ting Liu; Ting Liu; Tingyu Zhao; Tingyu Zhao; Ruili Dang (Frontiers in Neuroscience, 2023)
BackgroundAccumulating studies suggested that major depressive disorder (MDD) was closely related to metabolic syndrome (MetS). Important endogenous regulators fibroblast growth factors (FGFs) 19 and 21 were also reported to participate in psychiatric disorders. This study aimed to investigate the role of FGF19 and FGF21 in MDD and to explore the possible pathogenic mechanism of metabolic and cognitive dysregulation in depression.MethodsA total of 59 MDD patients and 55 healthy control participants were recruited. The serum levels of FGF19 and FGF21 and lipid profiles were measured by means of enzymatic methods. Cognitive function was measured by repeatable battery for the assessment of neuropsychological status (RBANS) scores. The gene expression of PGC-1α and FNDC5 was determined by quantitative polymerase chain reaction (PCR).ResultsWe found that plasma FGF19 and FGF21 levels were significantly decreased in patients with MDD. Meanwhile, triglyceride (TG) was significantly elevated and PGC-1α was significantly downregulated in MDD patients. Correlation analyses showed negative associations between TG and FGF19 levels. As for cognitive performance, both FGF19 and FGF21 levels were positively correlated with immediate memory. However, FGF19 levels were negatively correlated with language, and FGF21 levels were also negatively correlated with attention and delayed memory. Additionally, negative associations were found between FGF19 levels and PGC-1α. FGF21 levels were positively associated with PGC-1α and negatively associated with FNDC5.ConclusionThis study elucidated the role of FGF19 and FGF21 in MDD. MDD patients were confirmed to have metabolic and cognitive dysregulation, and this abnormality was linked to the decreased concentrations of FGF19 and FGF21 through the PGC-1α/FNDC5 pathway. Our results showed that the alterations of FGF19 and FGF21 levels may be a common pathogenic mechanism of metabolic and cognitive disturbances in patients with MDD.